Increasing Returns, Decreasing Returns and Regional Economic Convergence in the EU - Gianni Guastella; Francesco Timpano (European Regional Science Association (ERSA), 2012)
Regional economic development is driven by the accumulation of production factors. More traditional factors like labour and physical capital are accumulated under the law of diminishing returns. This, in turn, allows less developed regions to better perform. Recent branches of theoretical and empirical literature have paid attention to the role of increasing returns in an attempt to explain the persistence in regional economic disparities. Increasing returns are commonly attributed either to the accumulation of non- traditional inputs such as human and knowledge capital or to the presence of local externalities generated by the spatial concentration of economic activities. The aim of the present paper is to address the importance of both decreasing and increasing returns for the economic growth of European regions. While economies will definitively converge in the long-run if production is characterized by decreasing returns, divergence is the likely outcome in presence of increasing returns. As regional growth is probably the result of a combination of both, from a policy perspective it is important to understand where the sooner stops and the latter starts. In this paper the economic performance of 186 European regions is analysed by using the ordinary growth regression approach. An empirical specification which simultaneously accounts for the presence of both decreasing and increasing returns is derived. The study is intended to examine the extent to which regional development originates from the (un)balance between convergence, driven by diminishing returns and divergence, boosted by increasing returns. Results indicate that the accumulation of traditional inputs leads the economic development of less favoured areas while the presence of increasing returns plays a more crucial role in developed regions. More in the detail increasing returns seem to be generated by the accumulation of knowledge and human capital while there is no clear evidence of agglomeration externalities. By using a non-linear specification for the growth equation it is also found evidence of important threshold effects in entering the stage of development characterized by increasing returns. Regional development process is accordingly depicted as a far more complex process than what the simple dualism between increasing and decreasing returns may help to figure out, with very important implications for policy.
Keywords: R11; R58; 330; Regional Growth; Economic Convergence; Non-linear models